LOAD CONVEYING BELT SUPPORTED BY SCORBOT ER V PLUS ROBOT AND CONTROLLED THROUGH ELECTRONIC CIRCUIT SUPPORTED BY LDR AND RELAY - Bahceci, Ferhat (Istanbul Univ, Fac Engineering, 2010)
Mankind acts through his or her sense organs during his life. Signals coming from the senses are considered and logically processed and a behaviour or action is accordingly developed after the truest decision has been made. As for the automation system being in industry the motion detection duty belongs to sensors. In today's technology, all kinds of sensors are produced and submitted for the service of people. The aim focused in automation systems is to ensure the robot to perform the targeted work accurately and within the shortest time possible. Nevertheless, depending on the increase of requirements at the present day, it is among the aims of robots to carry out a true motion by making logical decisions in addition to this qualification. In this project, it is intended to lay down the load onto the requested point from 3 different points by classifying the load as per the size of the load through a logical algorithm by sensing the dimensions of load through sensors on the robot arm after having grabbed the load on the load convey belt through the robot arm Scorbot ER V Plus'' by creating of necessary control signals through sensors and relays.
Keywords: Robot; Load belt; LDR (Light dependent resistance); Relay; Automation